2009
DOI: 10.1097/mcg.0b013e31819359aa
|View full text |Cite
|
Sign up to set email alerts
|

Can the Growth Rate of a Gallbladder Polyp Predict a Neoplastic Polyp?

Abstract: Patient's age (>60 y) and large polyp size (>10 mm) were significant predictive factors for neoplastic GB polyps. GB polyps less than 10 mm in diameter do not require surgical intervention simply because they grow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
2
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 10 publications
1
27
2
13
Order By: Relevance
“…Numerous studies have subsequently validated or refuted this observation. 1,10,14,15,[20][21][22] In our study, an US size ≥10 mm was associated with malignancy, whereas an US size <9 mm had a 100% negative predictive value for malignancy. Zielinski et al 13 suggested operating on lesions >6 mm in size in order to increase the sensitivity for identifying malignant cases.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Numerous studies have subsequently validated or refuted this observation. 1,10,14,15,[20][21][22] In our study, an US size ≥10 mm was associated with malignancy, whereas an US size <9 mm had a 100% negative predictive value for malignancy. Zielinski et al 13 suggested operating on lesions >6 mm in size in order to increase the sensitivity for identifying malignant cases.…”
Section: Discussioncontrasting
confidence: 61%
“…Previous studies have reported that the following characteristics are associated with malignancy: advanced age, solitary and sessile polyps, rapid growth, presence of gallstones, history of primary sclerosing cholangitis (PSC), and presence of vascularity on US. 1,9,10,[12][13][14][15][21][22][23] We could not examine the association of PSC, solitary versus multiple lesions, or the growth rate with malignancy in our series. In our series, the presence of vascular flow on Doppler was not specific to malignant lesions.…”
Section: Discussionmentioning
confidence: 98%
“…However, the data on multivariate analysis proved that the growth rate was not related to the nature of a GPL [17]. Consequently, a new ultrasound imaging technique is required.…”
mentioning
confidence: 92%
“…In patients who were monitored with serial abdominal US, 86% of polyps did not change in size and 6% grew in size. Shin and colleagues 23 retrospectively reviewed 145 patients who eventually underwent cholecystectomy. They found that a growth rate of <6 mm/month had a negative predictive value of >90%.…”
Section: Resultsmentioning
confidence: 99%
“…However, on multivariate analysis the growth rate was not associated with malignancy, regardless of polyp size. Thus, the investigators concluded that GBP of <10 mm do not need to be removed simply because they grow 23 . Colecchia and colleagues 24 prospectively followed 56 patients with small GBP (<10 mm) over 5 years with annual abdominal US.…”
Section: Resultsmentioning
confidence: 99%